Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. -- From publisher's description. Contenu : Preface -- Acknowledgements -- About the author -- The study of gender -- Researching sex and gender -- Gender stereotypes: masculinity and femininity -- Hormones and chromosomes -- Theories of gender development -- Developing gender identity -- Intelligence and cognitive abilities -- Emotion -- Relationships -- Sexuality -- School -- Careers and work -- Health and fitness -- Stress, coping, and psychopathology -- Treatment for mental disorders -- How different? -- References -- Index.
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

Boundaried caring and gendered emotion management in hospice work - Cain, Cindy L. (Gender, Work and Organization, 2017)
Caring work, which is premised on caring for and caring about recipients, involves a great deal of emotion management. Feeling rules shape expectations about emotion management and are informally shared through workers’ narratives about quality work. Using qualitative data from hospice workers in the southwestern US, I find that narratives of quality within hospice include emotion-management skills such as listening, truly caring, keeping calm and maintaining boundaries. Through an analysis of how workers discuss and map skills onto individual women and men co-workers, this article highlights two gendered patterns. First, even when women and men are thought to share high-quality skills, the ways these skills are described reinforce naturalistic understandings of gender. Second, men are seen to hold a broad range of emotion-management skills, but women are not described as holding the most important emotion-management skill: keeping boundaries. Understanding this differential application of emotion-management skills helps us to understand how gender and gender inequality are reproduced within caring work. © 2017 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; intersectionnalité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; soins palliatifs; systèmes d'oppressions; thématiques; travail; travail du care; travailleureuses de la santé; émotions; états-unis

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

A visual analysis of gender bias in contemporary anatomy textbooks - Parker, Rhiannon; Larkin, Theresa; Cockburn, Jon (Social Science & Medicine, 2017)
Les recherches empiriques ont établi un lien entre les préjugés sexistes dans l’enseignement médical et les attitudes et comportements négatifs des prestataires de soins de santé. Pourtant, cela fait plus de 20 ans que les recherches n’ont pas examiné dans quelle mesure les femmes et les hommes sont représentés de manière égale dans les manuels d’anatomie . En outre, les recherches antérieures n’ont pas exploré au-delà de la quantité de représentation pour examiner également les stéréotypes visuels de genre et, à la lumière des avancées théoriques dans le domaine de la recherche intersectionnelle, la relation entre les représentations du genre et les représentations de l’ethnicité, du type de corps, de la santé et de l’âge. Cette étude visait à déterminer l’existence et la représentation des préjugés sexistes dans les principaux manuels d’anatomie utilisés dans les écoles de médecine australiennes. Une analyse systématique du contenu visuel a été menée sur 6044 images dans lesquelles le sexe/genre pouvait être identifié, provenant de 17 principaux manuels d’anatomie publiés entre 2008 et 2013. Une analyse de contenu plus approfondie a été réalisée sur les 521 images narratives, qui représentent une histoire en cours, trouvées dans les mêmes manuels. Les résultats indiquent que la représentation du genre dans les images des manuels d’anatomie reste majoritairement masculine, sauf dans les sections spécifiques au sexe. En outre, d’autres formes de biais ont été constatées dans : la visualisation d’émotions, de rôles et de contextes stéréotypés en fonction du sexe ; le manque de diversité ethnique, d’âge et de type corporel ; et dans l’adhésion presque totale à une conception binaire sexe/genre. Malgré une attention accrue portée aux questions de genre en médecine, la représentation visuelle du genre dans les programmes médicaux continue d’être biaisée. La construction biaisée du genre dans les manuels d’anatomie conçus pour l’enseignement médical fournit aux futurs prestataires de soins de santé des informations inadéquates et irréalistes sur les patients.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; australie; corps; discous dominant; intersectionnalité; livres d'anatomie; océanie; projet charge mentale; périodes historiques; racisme; représentation des corps; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques